Pengaruh Ketahanan Aus Baja SA 516-70 Setelah Mengalami Pelapisan Elektroda Sandvik 29 8 2 Lr Dan 25 10 4 Lr - Sidiq Ruswanto (Politeknik Negeri Ujung Pandang, 2008)
SA 516-70 is a low carbon steel which is used for marking of boiler, high pressure tank and heat exchanger. Steel of SA 516-70 is applied for corrosion and wear resistance equipment. Weld surfacing can be used to overlay new components to their original dimensions. All are welding processes can be used for overlay as well joining applications. In this research two types of electrodes used are Sandvik 25 10 4 LR and Sandvik 29 8 2 LR. Weld surfacing process was used GTAW process using DCEP. The welding parameter used are as follow: welding current between 110 A to 112 A, welding voltage between 12 to 13 volt and travel speed between 173 to 191 mm/ minute. The weldments was then conducted hardness testing, metallographic examination, EDAX and X-Ray Diffraction ( XRD ). Samples for hardness testing were taken from base metal and to the filler metal layer. EDAX testing was taken from metal to the outer layer layers, while XRD testing was conducted on the base metal, layer 1 and layers 3. The results that the high hardness value of 356 Hv was Found on at layer 1 using sandvik electrode 29 8 2 LR. The base metal microstructure was reveled some ferrite and pearlite structure.The cromium dilution using sandvik electrode 29 8 2 LR was higher than that of sandvik electrode 25 10 4 LR. From all data investigations was concluded that the usage of sandvik electrode 29 8 2 LR is better performance than use of sandvik electrode 25 10 4 LR.